THE ANALYSIS OF LEADERSHIP CHARACTER OF SNOW QUEEN OF ARENDELLE IN DISNEY MOVIE â€œFROZENâ€ - Soares, Geralda A. Lay X. F. (Program Studi Sastra Inggris, Fakultas Sastra, Universitas Komputer Indonesia Bandung, 2019)
Animated movie